CPC-116 Prevention of Opioid-Induced Constipation: Results from a Campaign in 4 Hospitals in Denmark. (12th March 2013) - Christensen, N
Abstract : Background: The Clinical Pharmacy Service is part of the Capital Region Pharmacy. The Clinical Pharmacy Service handles acquisition of medicines for the hospital wards and is responsible for the safe and rational use of medicines. The department employs teams consisting of a pharmacist and a pharmaconomist [roughly translating as an expert in pharmaceuticals] with responsibility for each ward. The educational background of the pharmaconomist is 3 years' tertiary education which includes an internship in a community pharmacy or hospital pharmacy. The pharmaconomist handles the daily acquisition of medicines and contact with the wards and the pharmacist is responsible for quality assurance. A campaign was launched to improve the quality of the service on the wards and to educate the pharmaconomists. Purpose: To improve awareness of opioid-induced constipation and treatment with laxatives. Materials and Methods: The pharmaconomist attended teaching sessions arranged by the pharmacists. The pharmacists developed an intervention handout to the wards containing information about why and how they should prevent opioid-induced constipation. For 8 weeks the pharmaconomists screened the medicines prescribed on the wards for opioids and checked whether a laxative was prescribed. If no laxative was prescribed they filled in an intervention handout with patient information and proposed solutions and gave it to a nurse or doctor on the ward. The nurse and doctor would consider the suggested solution and tick off either 'Yes I agree and have prescribed a laxative' or 'No I don't agree' and return the handout to the pharmaconomist. Results: A total of 2282 patient medicines were screened and 681 patients had been prescribed opioids. 236 of the patients receiving opioids did not have a prescription for a laxative and the pharmaconomist filled in an intervention handout for these patients. 25 interventions were accepted by the doctors on the wards and laxatives were prescribed. Unfortunately about 50% of the handouts were never returned to the pharmacy, making it difficult to determine the exact number of interventions accepted. Also a number of patients were discharged before action could be taken. If the intervention were to be repeated the following would be relevant to improve the outcome: better communication with the doctors, ensure that the patients on selected wards are hospitalised for a few days (to make time for intervention) and more time to prepare the ward personnel. Conclusions: The campaign was a success, but more could be done to improve the outcomes of such a campaign. It is important to consider the selection of wards to include in the campaign. On wards where the patients are discharged after a few days it can be difficult to implement the interventions under time pressure. No conflict of interest.